Bandgap Energy of TiO2/M-Curcumin Material (M = Na+, Mg2+, Cu2+) - Imelda Hotmarisi Silalahi; Risya Sasri; Peni Peni; Titin Anita Zaharah (Jurnal Kimia Sains dan Aplikasi, 2022)
Bandgap energy (Egap) of TiO2/curcumin as well as TiO2/M-curcumin (M = Na+, Mg2+, Cu2+) was determined. The material was prepared on transparent conductive oxide as TiO2 film. Then, the curcumin and curcumin derivatives were adsorbed on TiO2 surface by immersing the film in solution of the compounds. The diffuse reflectance UV-Vis spectra of the materials were recorded and utilized to calculate the Egap using the Tauc plot method. The calculation gave the Egap of TiO2 of 3.27 eV that lowers after being deposited with curcumin and metal-curcumin compounds. The Egap of TiO2/curcumin was 2.82 eV, while TiO2/Na+-curcumin, TiO2/Mg2+-curcumin, and TiO2/Cu2+-curcumin were 2.36, 3.11, and 2.15 eV, respectively. Curcumin metal complexes, i.e., TiO2/Cu2+-curcumin, showed high molar absorptivity and effectively deposited on the TiO2 lowers the bandgap energy of TiO2 compared to free-curcumin on TiO2.